Potential and Interaction Patterns of Utilization of Seagrass Fishery Resources in Tuduku Island, South Jailolo District, West Halmahera Regency - Rina, Rina; Darmawaty, Darmawaty; Abubakar, Salim; Kadir, Masykhur Abdul; Subur, Riyadi; Sunarti, Sunarti; Abubakar, Yuyun; Susanto, Adi Noman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
. Seagrass ecosystem is one of the coastal ecosystems that can provide food supply and improve the living standards of coastal residents. The objectives of the study were to determine the composition of the seagrass species on Toduku Island, to determine the composition of the seagrass biota species, to determine the community structure of seagrass species and associated biota including species diversity, species dominance and species density and to determine the interaction pattern of the utilization of seagrass fisheries resources by the community around Toduku Island. . The method used is field observation and Participatory Rural Appraisal (PRA). The composition of seagrass species in Toduku Island are Enhalus acoroides, Thalassia hemprichii, Halophila minor, Cymodocea rotundata, Halodule pinifolio, and Syringodium isoetifolium. The composition of the biota that inhabits the seagrass beds of Toduku Island consists of fish, crabs and macrozoobenthos (Holothuroidea, Echinoidea, Asteroidea, gastropods, bivalves). The diversity of seagrass and biota species is moderate, there is no dominant species and the distribution of each species is very even. The pattern of interaction in the use of seagrass resources has been patterned for generations. The forms of utilization activities carried out by the community include taking mollusks (snails, clams), echinodes (sea cucumbers, sea urchins), catching fish and crabs.